A sectoral explanation of per capita income convergence and divergence: estimating Verdoorn’s law for countries at different stages of development - Magacho, Guilherme R; McCombie, John SL (Oxford University Press (OUP), 2018)
This paper estimates the Verdoorn law (the relationship between productivity and output growth) for manufacturing industries for 70 developed and developing countries. It tests the hypothesis that the various manufacturing industries exhibit different values of the Verdoorn coefficient and hence different degrees of increasing returns, broadly defined. The paper analyses especially whether or not these estimates vary according to the level of a country’s economic development, controlling for such factors as human capital and the level of technology. It is found that this is the case. Countries in the early stages of development would benefit from specialising in low-tech manufacturing and consumption goods, as these industries have larger Verdoorn coefficients than in the more developed countries. However, as countries reach higher stages of development, it is advantageous for them to specialize in the high-tech manufacturing industries and the capital goods industries. These have relatively high values of the Verdoorn coefficient compared with the less developed countries. It is concluded that the composition of industries that leads to the fastest growth of manufacturing productivity differs depending upon the level of economic development.
Keywords: 38 Economics; 3801 Applied Economics; 3802 Econometrics; 8 Decent Work and Economic Growth